A High Potential of Biomass Leaves Waste for Porous Activated Carbon Nanofiber/Nanosheet as Electrode Material of Supercapacitor. (October 2020) - Apriwandi,; Agustino,; Taer, Erman; Taslim, Rika
Abstract: Since porous carbon materials derived from biomass, with low cost, abundant and sustainable, relatively easy fabrication, high electrical conductivity, large specific surface area (SSA), surface morphology with nanomaterial structures, and superior electrochemical stability have attracted attention which are strong and highly trusted to be a candidate for the electrode material of supercapacitor energy storage. This study highlighted recent laboratory-scale methods for preparing activated carbon nanostructures from leaves biomass wastes. Four types of focused leaves waste including acacia leaves, pineapple leaves, and Terminalia catappa leaves (TCL), and Pandanus tectorius leaves (PTL). Leave wastes were converted into activated carbon by KOH activation and one-stage integrated pyrolysis both of carbonization and physical activation. Symmetric supercapacitor electrode ware performed with sandwich-type in monolith form without adhesive materials. Among the raw materials found in this study, nanofiber structures dominated the surface morphology of carbon monolith, especially in acacia leaves, pineapple leaves, and TCL. Interestingly, the same basic material of TCL could perform two different nanostructures including nanofiber and nanosheet. In addition, the percentages of carbon and oxygen contents in the sample were also provided. Furthermore, supercapacitor cells exhibited the highest specific capacitance are activated carbon derived from pineapple leaves as high as 150 F g −1 in 1M H2 SO4 aqueous electrolyte at a low scanning rate of 1 mV s −1 . Finally, these results confirmed that leaves biomass wastes have high potential as a raw material of activated carbon nanofiber/nanosheet structure to be applied in supercapacitor electrodes.